Energy and emission performance of enhanced vapor injection air source heat pump system using low global warming potential refrigerants in different climate regions - Zhang, Libiao; Jing, Wuhui; Wang, Qilong; Zhang, Jianing; Yang, Peifang (Frontiers in Energy Research, 2023)
In order to meet the space heating requirement of residential buildings in low-temperature areas, the performance of the enhanced vapor injection (EVI) air source heat pump (ASHP) system and single-stage compression heat pump system (BASE) using low global warming potential (GWP) working fluids in low-temperature environment are studied. The thermodynamic and emission characteristic models of air source heat pump are developed and optimized, and further compared with traditional heating solutions when used in five different typical cities throughout the world. The results indicate among the selected working fluids, R152a achieves the highest COP of 3.91 among all of the selected low GWP working fluids. When the ambient temperature is 0°C, the maximum COP of the EVI system is 2.51 when CO2 is adopted, and the corresponding optimal discharge pressure and intermediate pressure are 10.57 MPa and 3.83 MPa, respectively. By exploring the changes of HSPF in five typical cities, the HSPF of the EVI system using CO2 is the most significant, which is 17.13%–26.69% higher than the BASE system. The most significant reduction of LCCP in EVI system using CO2 is 15.34%–26.66% compared with BASE system. For SO2 and NOX, the EVI system using R152a has a better emission reduction effect, which is 3.73%–64.73% and 3.72%–66.04% lower than the other solutions, respectively. This study can provide a theoretical reference for the application of low GWP heat pumps with EVI technology.